2006
DOI: 10.1901/jaba.2006.7-05
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Relative Effects of Feedback and Contingent Money for Staff Training of Stimulus Preference Assessments

Abstract: Performance feedback has facilitated the acquisition and maintenance of a wide range of behaviors (e.g., health-care routines, seat-belt use). Most researchers have attributed the effectiveness of performance feedback to (a) its discriminative functions, (b) its reinforcing functions, or (c) the combination of the two. In this study, we attempted to evaluate the relative contributions of the discriminative and reinforcing functions of performance feedback by comparing a condition in which the discriminative fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 29 publications
4
64
0
2
Order By: Relevance
“…Researchers have included video-based feedback as part of ongoing training and integrity-monitoring procedures with demonstrated success (i.e., Kissel, Whitman, & Reid, 1983;Roscoe, Fisher, Glover, & Volkert, 2006); the specific contribution of the video-based components has not been explored. For example, Robinson (2011) demonstrated that a training package consisting of modeling and video-based feedback was an effective means of teaching paraprofessionals to implement Pivotal Response Treatment.…”
Section: Research On Video-based Feedbackmentioning
confidence: 99%
“…Researchers have included video-based feedback as part of ongoing training and integrity-monitoring procedures with demonstrated success (i.e., Kissel, Whitman, & Reid, 1983;Roscoe, Fisher, Glover, & Volkert, 2006); the specific contribution of the video-based components has not been explored. For example, Robinson (2011) demonstrated that a training package consisting of modeling and video-based feedback was an effective means of teaching paraprofessionals to implement Pivotal Response Treatment.…”
Section: Research On Video-based Feedbackmentioning
confidence: 99%
“…There are numerous research studies that demonstrate the importance of frequent opportunities to respond and receive feedback during skill acquisition (e.g., Kritch & Bostow, 1998). For example, Roscoe, Fisher, Glover, and Volkert (2006) trained adults to implement preference assessments using written instructions, monetary rewards, and feedback. The participants did not complete the preference assessments procedures with 100% accuracy in either the written instruction or monetary reward conditions; however, when feedback was provided, either alone or with a monetary reward, preference assessment procedures were implemented correctly.…”
Section: Solutionsmentioning
confidence: 99%
“…For example, direct-care providers are not only responsible for recording data but also may be called upon to document preparation of care plans (Garrity & Luiselli, 2005) and perform preference assessments (Lavie & Sturmey, 2002;Roscoe et al, 2006). Key features of effective supervision, as evaluated in this study, appear to be giving staff behavior-specific action directives, monitoring performance through systematic feedback, and positively reinforcing progress towards and achievement of specified objectives.…”
Section: Resultsmentioning
confidence: 95%
“…Being a multicomponent intervention it is not possible to isolate the contribution of each procedure. In fact, most staff training interventions rely on multiple procedures applied simultaneously (Lavie & Sturmey, 2002;Moore et al, 2002;Shore, Iwata, Vollmer, Lerman, & Zarcone, 1995), although in some cases a singular method such a performance feedback can be effective (Leblanc, Ricciardi, & Luiselli, 2005;Reedy, Thibadeau, & Luiselli, 2001;Roscoe, Fisher, Glover, & Volkert, 2006).…”
Section: Performance Feedbackmentioning
confidence: 99%